Control of virulence by small RNAs in Streptococcus pneumoniae. - Beth Mann (Public Library of Science (PLoS), 2012)
Small noncoding RNAs (sRNAs) play important roles in gene regulation in both prokaryotes and eukaryotes. Thus far, no sRNA has been assigned a definitive role in virulence in the major human pathogen Streptococcus pneumoniae. Based on the potential coding capacity of intergenic regions, we hypothesized that the pneumococcus produces many sRNAs and that they would play an important role in pathogenesis. We describe the application of whole-genome transcriptional sequencing to systematically identify the sRNAs of Streptococcus pneumoniae. Using this approach, we have identified 89 putative sRNAs, 56 of which are newly identified. Furthermore, using targeted genetic approaches and Tn-seq transposon screening, we demonstrate that many of the identified sRNAs have important global and niche-specific roles in virulence. These data constitute the most comprehensive analysis of pneumococcal sRNAs and provide the first evidence of the extensive roles of sRNAs in pneumococcal pathogenesis.